Preparation and Characterization of Velvet Beans-Based Edible Film Fortified with Green Tea Extract as Antioxidant Agent - Noer Abyor Handayani; Laurensia Belinda Soewito; Alfan Fatir F; Ignatia Novita T; Tian Shifa S (Dept. of Chemical Engineering, Diponegoro University, 2022)
Health and environmental problems related to plastic food packaging are general problems. Edible film as food packaging from organic and edible materials can be a solution by increasing its structure and content. Modification of edible film from the protein of Velvet bean (Mucuna pruriens) with gelatin and alginate to modify the structure of the film and the addition of green tea leaf extract as an antioxidant. Edible films are made by combining constituent materials with the addition of a crosslink method. The addition of green tea leaf antioxidant concentration on nutritional properties, chemical properties, and shelf life of edible films through the DPPH method and antimicrobial tests showed good changes. The addition of gelatin, alginate, and green tea leaves to the mechanical and morphological properties of the film showed good indications. The effect before and after the addition of green tea leaves on the chemical structure of the edible film (OH‑ group) using FTIR analysis shows indications through changes in spectra. Modified velvet bean film with gelatin, alginate, and green tea leaves can potentially be applied in the food industry as food packaging.